PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM PENANGANAN PENGUNGSI DI KOTA PEKANBARU TAHUN 2017-2021 - Naufal Fadhila; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research is based on in International Relations, especially in contemporary concentration. The refugee problem is a social problem that is included in contemporary concentration in International Relations studies. The background of the appointment of the refugee case in this study related to the refugees demonstrations that occurred in several places in Pekanbaru City, namely at the office Kesbangpol city of Pekanbaru, the building Graha Pena Riau, the regional office of the Riau Ministry of Law and Human Rights and the office of the Governor Riau, from November 15th,2021 to November 2nd,2022. another is to demand UNHCR to immediately resettlement refugees to third country. This study used a qualitative research method with data triangulation from interviews with UNHCR, refugees, Kesbangpol Pekanbaru City, and the Pekanbaru City Community. Furthermore, to evaluate the role and find the root of the problem in this study, Clive Archer's theory of the role of International Organizations (OI) is used, which divides the role of International Organizations into 3 roles, 1.) the role of OI as an instrument; 2.) OI's role as an arena; and 3.) OI's role as an actor. The results of this study showed that UNHCR has carried out all of these roles. Therefore it was identified that the problem of resettlement demanded by refugees from UNHCR was a wrong understanding of UNHCR's role. This research showed that UNHCR has implemented an optimal role, such as UNHCR's role as an instrument, by through the Self-Reliance program in the form of Education Program (formal and informal), Livelihood and Income, and Access to Other Basic Human Rights; UNHCR's role as an arena, by becoming a place for meetings and consultations to resolve refugee problems; UNHCR's role as an actor is how UNHCR can influence and codify state decision-making so that it is in accordance with UNHCR's mandate. Besides that UNHCR has also carried out 14% resettlement in Pekanbaru City. Keywords: Role, UNHCR, Resettlement, Refugees, Refugees in Indonesia